Adaptive interaction and dementia : how to communicate without speech - Ellis, Maggie (Psychologist); Astell, Arlene (Jessica Kingsley Publishers, 2018)
Effective communication with people with dementia is imperative to good relationships with professional caregivers and family members. This book offers a person-centred approach to assessing the communication skills of people with dementia who are unable to speak, and presents evidence-based methods for effective non-verbal communication.